The Influence of Organizational Justice, Job Environment and Job Insecurity on Job Satisfaction of Honorary Employee in Bappeda Provinsi Jawa Tengah - Nurul - Hasannah; Karnowahadi - Karnowahadi; Eva - Purnamasari (Politeknik Negeri Semarang, 2021)
This study aims to the influence Organizational Justice, Job Environment and Job Insecurity on Job Satisfaction of Honorary Employee in Bappeda Provinsi Jawa Tengah. The data collection methods used in this research are questionnaire and observation. The sample in this research is 51 employees of Bappeda Provinsi Jawa Tengah. The sampling method is using simple random sampling method. Data analysis method used is multiple linear regression. The result of coefficient determination shows that Organizational Justice, Job Environment and Job Insecurity contribute 75,7% on Job Satisfaction of Honorary Employee in Bappeda Provinsi Jawa Tengah, and the rest is influenced by other factors that did not mentioned in this research. According to the result of this research, Job Insecurity did not influence Job Satisfaction, meanwhile Organizational Justice and Job Environment influence Job Satisfaction